Every Monday Mabel - Awan, Jashar (Simon & Schuster Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2025)
Every Monday Mabel takes her breakfast outside and waits for her favorite part of the week: the garbage truck.